Diseminasi Informasi Terkait Metode Kontrasepsi Jangka Panjang pada Masyarakat Desa Bunut Baok, Lombok Tengah - Harahap, Herpan Syafii; Danianto, Ario; Abdurrachim, Abdurrachim; Sartika, Baiq Dewi; Hiwala, Paniatul; Purwani, Luh Made Ita; Ratih, Ni Wayan Sekar; Putri, Nurarafah Andika; Susilawatin, Sri; Uzmi, Muhammad Azrul; Ackbar, Rifky Maulana; Dianggita, Vinni (Jurnal Gema Ngabdi, 2020)
Indonesia is the fourth most populous country in the world. In 2015, the population growth rate in West Nusa Tenggara is equal with national population growth rate, which is about 1.39%. The long-term contraceptive methods is one of the most effective family planning programs to succeed in controlling the population growth rate. The participation rate for the use of this contraceptive methods by fertile age couples in Bunut Baok village, Middle Lombok, is only about 10%. This was dissemination of information event aimed to disseminate the information regarding long-term contraceptive methods to Bunut Baok villagers, Middle of Lombok. This social event is part of the thematic Kuliah Kerja Nyata (KKN) programs of students of Universitas Mataram in the period of 2020 in Bunut Baok villagers attended by 59 Bunut Baok villagers as participants. In this event, pre-test and post-test were also conducted to evaluate the increase of their knowledge about long-term contraceptive methods. The participants had mean age of 36 years old, mostly female and had senior high school educational level. The mean of posttest scores was higher than the mean of pretest scores (88.54vs77.03; p = 0.000). These results indicated that this dissemination of information event increase the level of knowledge of Bunut Baok villagers related to the long-term contraceptive methods.